Sonic Hedgehog promotes the development of multipotent neural crest progenitors endowed with both mesenchymal and neural potentials - Calloni, Giordano W. (National Academy of Sciences, 2007)
In the vertebrate embryo, the cephalic neural crest cells (CNCCs) produce cells belonging to two main lineages: the neural [including neurons, glial cells of the peripheral nervous system (PNS), and melanocytes] and the mesenchymal (chondrocytes, osteoblasts, smooth muscle cells, and connective tissue cells), whereas the trunk NCCs (TNCCs) in amniotes yield only neural derivatives. Although multipotent cells have previously been evidenced by in vitro clonal analysis, the issue as to whether all of the mesenchymal and neural phenotypes can be derived from a unique NC stem cell has remained elusive. In the present work, we devised culture conditions that led us to identify a highly multipotent NCC endowed with both neural and mesenchymal potentials, which lies upstream of all the other NC progenitors known so far. We found that addition of recombinant Sonic Hedgehog (Shh) increased the number of CNCC progenitors yielding both mesenchymal and neural lineages and promoted the development of such precursors from the TNCC. Shh decreased the neural-restricted precursors without affecting the overall CNCC survival and proliferation. By showing a differential positive effect of Shh on the expression of mesenchymal phenotypes (i.e., chondrocytes and smooth muscle cells) by multipotent CNCCs, these results shed insights on the in vivo requirement of Shh for craniofacial morphogenesis. Together with evolutionary considerations, these data also suggest that the mesenchymal-neural precursor represents the ancestral form of the NC stem cell, which in extinct forms of vertebrates (the ostracoderms) was able to yield both the PNS and superficial skeleton.